2000
DOI: 10.1074/jbc.275.18.13637
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Targeting Signal-1 Receptor Protein PEX5 fromLeishmania donovani

Abstract: The human pathogens of the Leishmania and Trypanosoma genera compartmentalize glycolytic and other key metabolic pathways in unique subcellular microbodies called glycosomes, organelles related to the peroxisomes of mammals and yeast. The molecular machinery that carries out the specific targeting of glycosomal proteins to the organelle has not been characterized, although the bulk of glycosomal proteins contain the COOH-terminal tripeptide glycosomal peroxisomal targeting signal-1 (PTS-1) similar to the mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…Indeed, all the available data indicate that this domain displays "normal" hydrodynamic properties as can also be predicted by the tridimensional structure of the human TPR domains (11,28,44). Considering the high frictional ratio of human Pex5p observed in this work, it is thus evident that the N-terminal domain of Pex5p dominates the hydrodynamic properties of the full-length protein.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Indeed, all the available data indicate that this domain displays "normal" hydrodynamic properties as can also be predicted by the tridimensional structure of the human TPR domains (11,28,44). Considering the high frictional ratio of human Pex5p observed in this work, it is thus evident that the N-terminal domain of Pex5p dominates the hydrodynamic properties of the full-length protein.…”
Section: Discussionmentioning
confidence: 73%
“…In this context, the results available for Pex5p from L. donovani are particularly interesting. This protein also displays an abnormal behavior upon size exclusion chromatography, an observation that led to the conclusion that Pex5p from this organism is a tetramer (44). However, as emphasized in a later work, binding assays using a PTS1-containing peptide failed to demonstrate the existence of those tetramers (26).…”
Section: Discussionmentioning
confidence: 93%
“…A further comparison of all other known PEX5 sequences revealed that this conserved motif and, therefore, the long form of PEX5 are only found in mammals; plants (18,84) (Arabidopsis thaliana: AF074843); and protozoa Leishmania donovani (85) and Trypanosoma brucei (86) but not in Caenorhabditis elegans (C34C6.6) (87); Drosophila melanogaster (AAF45676.1); or different yeast species. For all species that share the common PEX7 binding motif there is evidence for PEX7 as in A. thaliana (AAF88113), or at least evidence for proteins with a PTS2 targeting signal as in plants and T. brucei (88).…”
Section: Domain Mapping Of Human Pex5mentioning
confidence: 99%
“…Among such proteins are PEX5, the receptor for the type 1 peroxisomal targeting sequence (10,11), and PEX2 (12), a protein required for peroxisomal protein import but whose exact function remains elusive. Also identified is a homologue of PEX11 (13), a peroxisomal membrane protein thought to function in fatty acid metabolism (14) as well as regulation of peroxisomal abundance (15).…”
mentioning
confidence: 99%